To dust [videorecording (DVD)] - Snyder, Shawn; Snyder, Shawn; Röhrig, Géza, 1967-; Broderick, Matthew, 1962-; Voit, Sammy (Cinedigm Entertainment, 2019)
After his wife's death, a Hasidic Jew becomes obsessed with the decomposition of her body and seeks out the help of a biology professor to understand the process.